Perceptions of the Teachers Towards EMI in the Public School in Surkhet - Chapain, Krishna Prasad (Exploration अन्वेषण, 2026)
The present study tries to explore the perception of the teachers in public schools adopting English as a medium of instruction in Surkhet district. I adopted a narrative enquiry with teachers of public schools in Gurbhakot Municipality who were adopting EMI for classroom teaching from grades one to ten for more than five years. For the study, a qualitative approach and a narrative inquiry method were used. For data collection, a public school was selected in Gurbhakot Municipality, and four teachers were selected purposively. For eliciting data, semi-structured interviews and classroom observation were used. Teachers of public schools who were practising EMI thought that, according to the interests of the parents and students and the global use of the English language, EMI is almost compulsory for the better career of the children, but there are some problems when adopting it. This study concludes that the teacher gave more preference to the English language because they know the importance of English as an international language.